2012
DOI: 10.1007/s10072-012-1065-2
|View full text |Cite
|
Sign up to set email alerts
|

Headache in patients with idiopathic intracranial hypertension: a pilot study to assess applicability of ICHD-2 diagnostic criteria

Abstract: Headache is one of the most common symptoms of idiopathic intracranial hypertension (IIH). The aim of this study was to investigate the applicability of the diagnostic criteria for "Headache attributed to IIH" included in the current classification of headache disorders, particularly as far as the main headache features. A consecutive clinical series of IIH patients with demonstration of increased intracranial pressure by lumbar puncture in the recumbent position were enrolled. Among a total of 22 patients, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…Tinnitus in IIH is usually bilateral and pulsatile in nature. It was reported by 51.8% of our patients similar to several studies that found tinnitus in 50-60% of their cases (2,22).…”
Section: Discussionsupporting
confidence: 91%
“…Tinnitus in IIH is usually bilateral and pulsatile in nature. It was reported by 51.8% of our patients similar to several studies that found tinnitus in 50-60% of their cases (2,22).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, some headache features usually attributed to migraine forms, and which are not among the required criteria for ''Headache attributed to IIH'', were present in some patients: pulsating quality and unilateral distribution of pain in around 20 %; migrainous associated symptoms in more than 40 % of the sample. As discussed in a previous paper [7] these observations may suggest that a migraine-like presentation of headache could be rather common in IIH patients.…”
Section: Discussionsupporting
confidence: 59%
“… 25–27 Migrainous features are particularly common (>70% of patients). 28 Our practice, particularly in those in whom headache is the principal complaint, is to evaluate the headache phenotype fully and to focus treatment towards the principal headache type. Those with chronic burnt-out disease—typically with stable vision and no or minimal papilloedema—often have the greatest headache disability.…”
Section: Managementmentioning
confidence: 99%